KEDUDUKAN HUKUM PERTUNANGAN ANAK DALAM HUKUM PERKAWINAN INDONESIA DAN KONVENSI HAK ANAK: STUDI KASUS DI SAMPANG, MADURA - Amara, Nikita Vitra; Sa’adah, Karomatu; Putri, Riska Widia; Setiawasih, Eva; Zendhy, Dhenya Myrelta; Putri, Desty Amanda; Hidayah, Astika Nurul (USRAH: Jurnal Hukum Keluarga Islam, 2025)
Child engagement is still a common practice in Indonesia, especially in areas with strong social and cultural norms. This article aims to analyze the legal status of child engagement in Indonesian marriage law and its compliance with the Convention on the Rights of the Child, with a case study in Sampang, Madura. This study uses a normative legal method with a legislative approach and case study. The results of the study show that although engagement does not have binding legal consequences in the national legal system, this practice is often the basis for submitting marriage dispensations, which ultimately increases the number of child marriages. This is contrary to Law Number 16 of 2019 which sets the minimum age for marriage at 19 years and the principle of the best interests of the child in the Convention on the Rights of the Child. This study emphasizes the need to strengthen regulations and public education to prevent the practice of child engagement and the negative impacts it causes, including the risk of exploitation and disruption of child development. Keywords:  Child Engagement; Marriage Law; Marriage Dispensation; Convention on the Rights of the Child; Child Protection.